The nature, extent and functional impact of foot problems in established rheumatoid arthritis - Gosai, Hema (My University, 2009)
Introduction Foot involvement is common in rheumatoid arthritis (RA). Foot pain, instability and deformity affect ambulation and impacts on health-related quality of life. The aim of this study was to determine the nature, extent and functional impact of rheumatoid foot problems in established RA. Patients and Methods One hundred RA patients were studied. Functional status was evaluated using the modified Health Assessment Questionnaire (mHAQ) and Foot Health Status Questionnaire (FHSQ). Foot deformity and footwear suitability was assessed using the Foot Problems Survey (FP Survey) and Footwear Suitability Scale (FWS Scale). Results In this predominantly female group of 95%, with a mean (± SD) disease duration of 12.2 (7.9) and moderate functional disability [mHAQ: 1.3 (0.6)], the FP Survey showed all patients had one or more foot deformity. Foot function was impaired with a mean (± SD) FHSQ score of 41.3 (12.4) and the FWS Scale showed that 93% wore unsuitable footwear. A strong correlation was observed of the global FHSQ (r=-0.5489, p<0.0001), its pain domain (r=-0.472, p<0.0001) and foot function domain (r=-0.599, p<0.0001), with the global mHAQ score. Despite the high frequency of foot problems observed only 27% had visited a podiatrist. Conclusion In conclusion foot problems and foot function disability is common in Black South African patients with established RA. Furthermore the strong correlation between mHAQ and FHSQ showed that foot functional disability was a major driver of overall functional disability in RA.
M.Sc.(Med.), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: foot problems; rheumatoid arthritis